BumbleKey: an interactive key for the identification of bumblebees of Italy and Corsica (Hymenoptera, Apidae) - Cappellari, Andree (Zookeys, 2018)
Abstract. BumbleKey is a matrix-based, interactive key to all 45 species of bumblebees of Italy and Corsica. The key allows to identify adult males and females (queens and workers) using morphological characters. The key is published online, open-access, at http://www.interactive-keys.eu/bumblekey/default.aspx.